Journal Sistem Pakar Deteksi Jenis Penyakit Gangguan Kejiwaan Menggunakan Metode Demster Shafer - wanda noor afrida; Samsir; Subagio, S (U-NET Jurnal Teknik Informatika, 2025)
An Expert System can be interpreted as a composition of data and information obtained from an expert or experts which is then processed by a system to be able to solve a problem according to the method used by experts or experts. One of the applications of expert systems is in the medical field, namely in the diagnosis of disease. In the research carried out, the design and creation of an expert system was created as problem solving to help diagnose mental disordersschizophrenia which begins with determining the symptoms to determine the type of mental disorder. In its design, this expert system uses the Simple Additive Weighting algorithm to determine the weight of each symptom experienced by the patient. Then the algorithmDempster Shafer to calculate the confidence value for the symptoms experienced by the patient.